Design of Sound Level Meter Using Sound Sensor Based on Arduino Uno - Lapono, Laura Anastasi Seseragi; Pingak, Redi Kristian (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2018)
Sound Level Meter (SLM) is a tool used to measure the noise level for a moment. For improved performance, hence required a measure of noise level capable of displaying result automatically on the computer so that simplify user to observe and measure the noise. In this study, the design system of data acquisition consists of a MAX4466 sound sensor, Arduino UNO microcontroller, and computer to display the measurement result. The measurement results are displayed in the form of data and graphs. The display of software designed using the Delphi 7.0. The process of taking data in the room with a sound intensity of 44.6 dB. The value is the measurement result using the SLM tool, while the measurement results using the sound sensor performed every second during an interval of 30 seconds obtained an average of 44.19 dB. It can be seen that between the two results shows a relatively small difference, so it can be concluded that the design of this system is running well. Keywords: Noise, SLM, Sound sensor, Arduino Uno